Media Literacy: A Prime Need Amid The Covid-19 Pandemic - Dhadwal, Yukti (The journal of contemporary issues in business and government, 2021)
In today‟s media saturated world, every individual requires to understand how to digest media. Media in its various forms is surrounding us in our daily lives. The maximum time is spent immersed in media whether in the form of listening radio, music, watching television or reading a magazine, newspaper or surfing internet. The various forms of media consumption are impacting us at an unprecedented rate. It has become extremely important to explore the various tools needed to effectively navigate the various forms of media. Media literacy has become necessity as it helps to develop the skill to analyse, evaluate and understand the media content. Amid the Covid-19 pandemic, the fake news is spreading like wildfire and media literacy is helping the citizens to develop the necessary skills to understand and critique messages that are received through television, film, print media, and the Internet. Media literacy is closely related to education. The ability to recognise multiple forms of media and identify the message they are communic ating is media literacy. Today, every citizen receives a massive amount of information from a large variety of outlets, way beyond conventional media such as TV, radio and newspapers; there are text messages, memes, viral images, social media, and much more. The misinformation and disinformation during COVID-19 pandemic is observed globally.[9] At present, it has become easiest to spread wrong information within a fraction of second and here, digital literacy comes at rescue. There are numerous online platforms for debunking fake information, such as altnews, boomlive, webqoof, vishwasnews, factly, smhoaxslayer, etc. which have become very helpful. This research paper attempts to understand the importance of media literacy during the pandemic. It also reviews the fake information which went viral on various online platforms and was debunk on online websites with proper facts. Keywords: Media literacy, corona pandemic, infodemic, misinformation, fake news.